2022
DOI: 10.24912/jpa.v4i3.19738
|View full text |Cite
|
Sign up to set email alerts
|

Faktor – Faktor Yang Mempengaruhi Initial Public Offering Underpricing

Abstract: This research was conducted to analyze the influence of the Auditor's Reputation, Intellectual Capital Disclosure, Profitability and Leverage on IPO Underpricing. The data used in this study were taken from the company's prospectus at the time of the initial public offering which was available on the Indonesia Stock Exchange website. There are 70 samples tested, consisting of companies that made initial public offerings in the 2017-2019 period. The sample data collection technique used purposive sampling. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Hal ini mengakibatkan emiten seringkali menentukan harga saham yang dijual pada pasar perdana dengan membuka penawaran harga yang tinggi, karena menginginkan pemasukan dana semaksimal mungkin. Sementara itu, underwriter sebagai penjamin emisi berusaha untuk meminimalkan risiko agar tidak mengalami kerugian akibat tidak terjualnya saham-saham yang ditawarkan (Apriliyanti, 2019;Hapsari & MAHFUD, 2012;Ningrum, 2015).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Hal ini mengakibatkan emiten seringkali menentukan harga saham yang dijual pada pasar perdana dengan membuka penawaran harga yang tinggi, karena menginginkan pemasukan dana semaksimal mungkin. Sementara itu, underwriter sebagai penjamin emisi berusaha untuk meminimalkan risiko agar tidak mengalami kerugian akibat tidak terjualnya saham-saham yang ditawarkan (Apriliyanti, 2019;Hapsari & MAHFUD, 2012;Ningrum, 2015).…”
Section: Pendahuluanunclassified
“…Pahlevi (2014) menyatakan bahwa semakin tinggi reputasi underwriter maka mengakibatkan tingkat underpricing semakin kecil. Hal ini dikarenakan underwriter lebih sering berhubungan dengan pasar modal sehingga mempunyai pengalaman yang lebih banyak mengenai pasar modal dibandingkan dengan emiten (Apriliyanti, 2019;Ayuwardani & Isroah, 2018;Pahlevi, 2014;Wahyusari, 2013). Apabila suatu emisi saham dilakukan oleh underwriter yang mempunyai reputasi bagus, maka saham yang dijamin oleh underwriter tersebut dapat mendatangkan kesukseskan bagi emiten.…”
Section: Uji Normalitas Dataunclassified
“…Research conducted by Mulyani and Maulidya (2021) shows that the reputation of KAP has a negative and significant effect on underpricing. Laurus & Setijaningsih, (2022) found that the importance of KAP has a negative and significant impact on underpricing. As well a study conducted by Setya & Fianto (2020), Riyanti (2021), andPratiwi et al (2020) stated that the reputation of KAP has a negative and significant effect on underpricing.…”
Section: The Effect Of Public Accounting Reputation On Stock Underpri...mentioning
confidence: 99%